(Re)constructing the Notion of Identity in Jhumpa Lahiri’s Interpreter of Maladies: A Diasporic Study of Selected Stories - Shahid Khan, Farkhanda (Linguistics and Literature Review, 2023)
The current study poses its focus on the complexities of diasporic tensions, especially concentrating on the reductive methods, contributing towards the homogenization of the formed and consolidated cultural and national identities. The concept of nationalism has often been utilized by third-world countries to express their views of cultural hegemony. However, the current research aims to provide an alternate perspective concerning globalization and cosmopolitanism. Furthermore, this study presents a diasporic picture of Lahiri’s characters celebrating multiculturalism and transnationalism. This study draws its foundation from Postcolonialism as a theoretical framework along with other concepts of leading theorists to conduct a close textual analysis of the selected works. Moreover, this study aims to analyze the representations of cultural and national identities in the characters of the selected text whom Lahiri puts in the in-between space of nation and identity, where they represent multiple cultures and histories. By so doing, Lahiri rejects the appeal to original accounts, which unfold cultural identities, while attempting to break and reconstruct the foremost chronicle of the nation. In the selected text, the Interpreter of Maladies (1999) nation and home are re-imagined not as a monolithic or stagnant space but rather as a precisely created structure, transformed and confronted, and resultantly shaping identities in a struggle. Consequently, the re-constructed diasporic approach unveils a deep crack in the consolidated unity and arises, instead, with multiple identities, which in Lahiri’s terms must be accepted, while coming out of the rhetoric of nationalism.